Gender-related discourses in corporate annual reports: an exploratory study on the Bangladeshi companies. Issue 3 (8th February 2021) - Hossain, Dewan Mahboob; Alam, Md. Saiful; Mazumder, Mohammed Mehadi Masud; Amin, Al
Abstract : Purpose: The purpose of this study is to explore the gender-related discourses in the annual reports of the listed companies in Bangladesh. Design/methodology/approach: To fulfill this objective, a sociological discourse analysis (SDA) of the gender-related texts in the annual reports of Bangladeshi companies (listed in the Dhaka Stock Exchange) was conducted. Sandberg and Holmlund's (2015) organizational impression management tactics (description, praise, admission, defense and writing styles) was applied as the analytical framework of SDA. The findings of the study were interpreted from a triangulation of two different theories: legitimacy theory and impression management theory. Findings: The study suggests that the companies in Bangladesh are disclosing gender-related information to a limited extent. They provide some information in relation to equal opportunities, business activities targeted to women and corporate contribution to women's welfare. Most of these gender-related discourses are rhetorical in nature. The companies used various impression management tactics such as description, praise, positive writing style, vague writing style and emotional writing style. Research limitations/implications: This study is exploratory in nature and focuses on cross-sectional data. Thus, it does not identify the trend of corporate gender reporting over the years. Practical implications: At the policy level, the findings revealed a need for reporting guidelines for gender narratives. Although there is a global gender reporting guideline as proposed under global reporting initiative, there is no local guideline in Bangladesh. Our findings suggest that in the absence of proper directives, companies presented facts and figures rhetorically and qualitatively. Social implications: Our findings provide valuable insights for the companies in assisting the Government of Bangladesh to deal with the prevailing gender inequality and achieved gender-related sustainable development goals. It is argued that the government should take more interest in corporate social responsibility activities (such as promoting gender equality) and introduce legislation and guidelines for social accounting. Originality/value: This is one of the very few studies that illustrate the corporate gender reporting of a developing economy – Bangladesh. To make a unique contribution to corporate gender disclosure, the study has drawn its analysis from a triangulation of the impression management and the legitimacy perspectives. Also, the use of SDA for annual report analysis has informed the readers about "how" the corporate narratives are presented in the annual reports rather than "what" issues are disclosed as commonly done in content analysis.